WACANA GUNOTTAMA DALAM GAGURITAN UNUH GALIH - Asri Artini, Ni Luh Alit (S2 Ilmu Linguistik Fakultas Ilmu Budaya Universitas Udayana, 2016)
AbstractThis study analyze Gunottama discourse in Gaguritan Unuh Galih (GUG). The composition of this gaguritan is dominated by the theme of Gunottama (various life’s learning values, teach yet enlighten us that in living this life). The focus of this research are to reveal the form of Gunottama, its function, and its meaning in Gaguritan Unuh Galih. Narrative discourse theory from Torodov is used to analyze the form of the Gunottama’s discourse. A Semiotic Theory from Peirce moreover will be used to interpret the discourse in the text. The most renowned sociology theory composed by Wellek and Warren will also be inserted as a main theory to analyze the function of the Gunottoma’s discourse in GUG. Basically Gunottama is harmonization among all well-beings to get the equilibrium in life.AbstrakPenelitian ini menganalisis teks Gaguritan Unuh Galih (GUG). Komposisi gaguritan ini lebih banyak membicarakan ajaran-ajaran penyadaran terhadap masyarakat Bali dalam GUG. Fokus penelitian ini untuk mengungkapkan bentuk, fungsi, dan makna gunottama dalam GUG. Teori yang digunakan untuk menganalisis bentuk wacana gunottama adalah teori wacana naratif dari Torodov. Untuk menginterpretasi teks adalah teori semiotika Peirce, teori sosiologi sastra Wellek dan Warren digunakan untuk menganalisis fungsi wacana gunottama dalam GUG. Gunottama dalam GUG pada intinya merupakan ajaran penyadaran untuk mencapai keharmonisan hidup.